Implementasi Pelaksanaan Perizinan Berusaha Bagi Usaha Mikro Kecil Dan Menengah di Kota Surakarta Melalui Online Single Submission Risk Bassed Approach - Dhea Putri Sri Wahyuniarti; Lego Karjoko; Rosita Candrakirana (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The importance of business licensing as a matter of legality is a manifestation of legally valid permits given by the government to business actors to carry out their business officially. The birth of the Job Creation Law gave birth to a business licensing system which previously contained the Online Single Submission system version 1.1 which was later developed into a risk-based approach/RBA or based on the level of risk of the business to be carried out. The aim of this research is to determine the implementation of business licensing for Surakarta City MSMEs through the Online Single Submission Risk Bassed Approach. This research method is empirical juridical legal research and uses a qualitative approach. This research uses primary data and secondary data. The primary data obtained came from interviews conducted at the Surakarta City Investment and One Stop Integrated Services Service. Then supported by secondary data obtained from library materials. Due to the convenience of the OSS-RBA system, system errors often occur or the server goes down, thus hampering the goal of facilitating business licensing, becoming a barrier for business actors to issue their business permits quickly. These obstacles make it difficult for business actors to log in or register on the OSS page, which means that the NIB is not immediately published. And many business people are still confused about the process flow for using OSS-RBA and are still blind to internet technology. However, despite these obstacles, the Surakarta City DPMPTSP has made various efforts to improve the quality of business licensing services in the City of Surakarta.